IMPLEMENTATION OF ASI (AUDITORY VISUAL SELF IMPROVEMENT) MODEL THROUGH DIGITAL VISUALIZATION MEDIA FOR LEARNING TO READ POETRY IN ELEMENTARY SCHOOLS - Imroatul Mufidah; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the effect of the ASI (Auditory Visual Self Improvement) model through YouTube digital visualization media to improve students’ poetry reading skills in elementary schools. This research is a classroom action research method, which consisted of two cycles. Each cycle consists of planning, action, observation, and reflection. The results of research in each cycle indicate an improvement. Classically, students were declared to have completed 100% of learning in cycle II, because all students in reading poetry achieved 80 or above. This learning completeness is above the KKM target of 80%. Based on these proportions, the criteria for qualitative data assessment are classified as